Complex surface modeling : methods, algorithms and applications - Chen, Wenyu (2011)
Nowadays, three dimensional (3D) movies, such as “Avatar”, “Clash of the Titans” and “How to Train Your Dragon”, are leading the film industry into the 3D era. One supporting element behind the amazing scenes of the 3D movies is the complex surface. Apart from the film industry, complex surfaces have intensive applications in CAD/CAM, Biomedicine, and Interactive & Digital Media (IDM). These applications require efficient and robust methods for modeling of complex surfaces.